The Book of Baruch by the Gnostic Justin, Geoffrey Hill (2019). Issue 2 (1st December 2020) - Wheale, Nigel
Review of: The Book of Baruch by the Gnostic Justin, Geoffrey Hill (2019)Oxford: Oxford University Press, 148 pp., ISBN 978-0-19882-952-2, h/bk, £20.00